Didattica inclusiva dell’italiano L2/LS tra lingua e identità di genere - Cerrato, Daniele (Studia Romanica Posnaniensia, 2024)
In some cases, the teaching of Italian as an L2/LS language continues to perpetuate gender stereotypes, sexist or discriminatory elements. When this is not the case, however, it often fails to offer those approaching the study of Italian the tools and materials to address relevant issues and themes in the contemporary debate such as gender identity and the importance of using inclusive language. Aware that the didactics of Italian can be a fundamental tool for building a context of coexistence of differences, we want to reflect on the Italian situation and present some didactic proposals that can allow to combine in the Italian classroom a language education a reflection on gender identity.